Variation in Tree, Foliage, Phenological and Pollen Characters of Low Chill Peach Germplasm Accessions under Mid-hills of Himachal Pradesh - Singh, Dinesh; Yepthomi, Gracely Y.; Kumar, K. (International Journal of Bio-resource and Stress Management, 2023)
The present investigation was carried out in the department of Fruit Science, Dr Y S Parmar University of Horticulture and Forestry, Nauni, Solan, HP, India. Ten peach genotypes namely TropicSweet, Saharanpur Prabhat, Earli Grande, Flordaprince, Tropic Snow, Flordaglo, Valle Grande, Tropic Beauty, Pratap and Florda Grande were evaluated for their tree, foliage, floral and pollen characteristics. Valle Grande recorded maximum tree height (2.73 m) whereas, minimum tree height (1.83 m) was recorded in Flordaprince. Shedding of leaf started from 29th October (Tropic Sweet) and extended till 20th November (Tropic Beauty). Time of full bloom extended from 24th January in Saharanpur Prabhat and Pratap to 2nd February in Tropic Snow and Flordaglo. The longest duration (39 days) of flowering was recorded in Pratap and shortest (28 days) in Tropic Sweet and Earli Grande. Pollen viability ranged from 93.82% to 98.93% when tested by 1.0% acetocarmine and 84.19 to 97.70% by 0.1% erythrosin B. In vitro pollen germination varied from 62.26% to 90.39%.